HUMANS AND SAGO TREES (A CONTEXT OF THEOLOGY EDUCATION ABOUT MYTHS OF THE CREATION OF HUMANS FROM SAGO TREES) - Novistianus D. Salenussa; Leonardo S. Pariama; Beatrix J.M. Salenussa (Peneliti.net, 2019)
This writing aims to provide a contextual description of theology of human nature, through the myth of the creation of humans from sago trees, whose process starts from examining the basic values ​​of the myth, in order to uncover the basics of arguments and cultural concepts that live within the Nuaulu tribe. The research method used in this article heurestikum with this type of research is the study of literature and interviews to collect and complete the data in order to develop the analysis received from key informants to be a source of information. Furthermore, cultural hermeneutics is carried out, which leads to an interpretation of the structure and mythical narrative of the Nuaulu tribe, namely, the creation of humans from sago trees. The results show that myth is seen as an ethnographic narrative of literature which through a hermeneutical pattern without relating other approaches can be used as a framework for contextual theology. This concludes that the myth of the creation of humans from the Sago tree, contains a set of codes or theological symbols that can be transformed in church life and society, to be used as a media or framework for constructing contextual theology in Maluku, through a set of theological values ​​rooted in the practice of sago, among others: unity, tenacity, hard work, discipline, economic orientation, life and togetherness. So that physiologically, the value structure of the sago tree leads to the formation of human identity.